Two-dimensional shear-wave elastography: a new method comparable to acoustic radiation force impulse imaging? - Schellhaas, Barbara; Strobel, Deike; Wildner, Dane; Görtz, Rüdiger; Neurath, Markus; Pfeifer, Lukas (European Journal of Gastroenterology & Hepatology, 2017)
OBJECTIVES: Two-dimensional shear-wave elastography (2D-SWE) is an ultrasound-based technique for the noninvasive assessment of tissue stiffness. In contrast to the well-established point-shear-wave elastography (pSWE) method acoustic radiation force impulse imaging, there is little evidence on the performance and usefulness of 2D-SWE in the assessment of liver stiffness. Thus, the aim of our study was to compare 2D-SWE versus pSWE. MATERIALS AND METHODS: 2D-SWE and pSWE were performed in 20 cirrhotic patients, 20 healthy individuals and an elasticity phantom. Stiffness values, examination time and number of measurements were compared. For 2D-SWE, the influence of size of the region of interest (ROI) was assessed. RESULTS: Elastography values in healthy individuals were slightly higher for 2D-SWE versus pSWE (1.4 m/s, range: 1.21-1.68 vs. 1.23 m/s, range: 1.07-1.39). In cirrhotic patients, there were no significant differences (3.06 m/s, range: 1.83-5.35 vs. 3 m/s, range: 1.67-4.37 m/s). Examination times were significantly longer for 2D-SWE in both patient groups (mean values for healthy/cirrhotic patients: 129.6/157.1 vs. 75/71.6 s). For 2D-SWE, variation of ROI size (5, 10, 20 mm) produced comparable results. After eight measurements, 90% of cirrhotic patients showed less than 5% of deviation from the results after the gold standard of 10 measurements; for healthy individuals, this was observed after six measurements. CONCLUSION: 2D-SWE seems to be comparable to pSWE (acoustic radiation force impulse-imaging) in cirrhotic patients, with slightly higher values in healthy individuals. 2D-SWE measurements require considerably more time. For 2D-SWE, ROI size seems to be of minor importance; multiple measurements should be obtained as single measurements differ. These preliminary results should be confirmed in larger patient collectives with histology as the reference standard.
EVALuna2:33813